2018
DOI: 10.1111/aor.13120
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evoked Potential Recovery by Subretinal Implantation of Photoelectric Dye‐Coupled Thin Film Retinal Prosthesis in Monkey Eyes With Macular Degeneration

Abstract: Retinal prosthesis or artificial retina is a promising modality of treatment for outer retinal degeneration, caused by primary and secondary loss of photoreceptor cells, in hereditary retinal dystrophy and age‐related macular degeneration, respectively. Okayama University‐type retinal prosthesis (OUReP) is a photoelectric dye‐coupled polyethylene film which generates electric potential in response to light and stimulates nearby neurons. The dye‐coupled films were implanted by vitreous surgery in the subretinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In our previous study, implantation of the photoelectric dye-coupled polyethylene lm in retinal dystrophic RCS rats led to vision recovery in the behavior test [14,29], and induced electroretinographic and visual evoked potential responses [29,30]. We also showed that the amplitude of visual evoked potential, which was reduced by macular degeneration in monkey eyes, was recovered by subretinal dye-coupled lm implantation [31]. The durability of dye-coupled lms in the subretinal space of monkey eyes was assessed for half a year [31].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In our previous study, implantation of the photoelectric dye-coupled polyethylene lm in retinal dystrophic RCS rats led to vision recovery in the behavior test [14,29], and induced electroretinographic and visual evoked potential responses [29,30]. We also showed that the amplitude of visual evoked potential, which was reduced by macular degeneration in monkey eyes, was recovered by subretinal dye-coupled lm implantation [31]. The durability of dye-coupled lms in the subretinal space of monkey eyes was assessed for half a year [31].…”
Section: Discussionmentioning
confidence: 61%
“…We also showed that the amplitude of visual evoked potential, which was reduced by macular degeneration in monkey eyes, was recovered by subretinal dye-coupled lm implantation [31]. The durability of dye-coupled lms in the subretinal space of monkey eyes was assessed for half a year [31].…”
Section: Discussionmentioning
confidence: 83%
“…In our previous study, we showed the recovery of visual evoked potential amplitudes in monkey eyes with macular degeneration by subretinal dye-coupled film implantation in the period of 6 months [36]. The dye-coupled film was also implanted in eyes of dogs [37] and rabbits [38, 39] to show the safety and surgical feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…Toshihiko Matsuo et al of the Okayama University Medical School and Graduate School of Medicine, Dentistry, and Pharmaceutical Sciences, Okayama City, Japan, reported on their retinal prosthesis (OUReP) which consists of a photoelectric dye‐coupled polyethylene film which generates electric potential in response to light and stimulates nearby neurons. The dye‐coupled films were implanted by vitreous surgery in the subretinal space of monkey eyes with macular degeneration which had been induced.…”
Section: Visual Supportmentioning
confidence: 99%